PERKAWINAN BEDA AGAMA DALAM PERSPEKTIF KEPASTIAN HUKUM PASCA TERBITNYA SURAT EDARAN MAHKAMAH AGUNG NOMOR 2 TAHUN 2023 - Mahbub Ali, Amum (Staisman Press, 2023)
The purpose of this study is to analyze several regulations related to marriage between people of different religions in Indonesia, especially based on the regulations of Marriage Law No. 1 of 1974 concerning Marriage, Law No. 23 of 2006 concerning Administration and Supreme Court Circular No. 2 of 2023 concerning instructions for judges in order to adjudicate cases of applications for registration of marriages between people of different religions and beliefs. In addition, it is also to explain how the legal certainty of marriage between people is after the issuance of SEMA Number 2 of 2023. Research methods used by analyzing literature data qualitatively through legal and conceptual approaches on legal certainty of marriage between people of different religions. The results showed that Law No. 1 of 1974 as amended by Law No. 16 of 2019 concerning Marriage does not regulate firmly and clearly about interfaith marriage. Article 2 paragraph 1 of the regulation only states whether or not marriage is valid and not submitted based on the law of their respective religions and beliefs, Article 35 (a) of Law No. 23 of 2006 which is a reference for judges in determining marriage between people of different religions contrary to the marriage law, there is a discrepancy between the two regulations that causes uncertainty in the law of marriage between people of different religions in Indonesia. The issuance of SEMA No. 2 of 2023 provides fresh air in an effort to end the polemic of marriage between interfaith couples in Indonesiaso that there is certainty and similarity in the application of law related to cases of marriage registration applications carried out by couples of different religions, even though the problem of marriage between people of different religions has not ended because article 35 (a) of Law No. 23 of 2006 concerning Administration and its explanation is still valid today.